PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN KUALITAS STRATEGI BISNIS TERHADAP KEUNGGULAN BERSAING DALAM MENINGKATKAN KINERJA UNIT (Studi Bank BNI Kantor Wilayah 05) - Siregar, Apriany Prima (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2016)
The purpose of this research is to test the influences of CRM and quality of bussiness strategy oncompetitive advantage to increase company performance. Using these variables, the usage of these variables are able to solve the arising problem within PT. Bank BNI Central Java.The samples size of this research is145manager PT. Bank BNI Central Java. Using the Structural Equation Modeling (SEM). The results show that the CRM and quality of bussiness strategy positive significant oncompetitive advantage to increase company performance.The effectCRM on competitive advantage are significant; The effectCRM and quality of bussiness strategy on competitive advantage are significant; The effect CRM on company performance are significant; the effect CRM and quality of bussiness strategy on company performance are significant, and The effect competitive advantage on company performance are significant.